The Correlation between Online Peer Review and Academic Writing Students’ Learning Styles - Emilia Ninik Aydawati; Dwi Rukmini; Dwi Anggani Linggar Bharati; Sri Wuli Fitriati (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
Peer review studies have been done for years. It has been found that by having these activities, learners will get benefits from the communication with the peer who can give them input to improve their writing performance. Peer review can be done face to face or online.  Face to face peer review is done synchronously where two students are having discussion on their essay, whereas online peer review can be done synchronously or asynchronously. This preliminary study investigates how the application of synchronous online peer review in Academic Writing class can be implemented to help them to do revision and improve their writing skills. The participants of this study is 50 students of academic writing class from two different class.  This is an experimental study where the students were treated to get peer review activities from the software which is uploaded in   web. They did the practice twice with the shuffled questions. This was aimed that they would be ready to give review.  Pre-test and post-test were conducted and Gracian questionnaire to know their learning styles was uploaded in the web for them to fill in order to know their learning styles. it was found out that there are some improvement and there is correlation between their academic skills and the learning styles.